KOMUNIKASI LANSIA DAN PENGEMBANGAN KECAKAPAN DIGITAL - Astrid, Andi Fauziah (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2022)
This study used the Social Inoculation method by looking at the digital iteration ability of the elderly. For several weeks, several elderly people from the city of Makassar were observed and interviewed, especially on the issue of hoax information they found. As a result, some already have the ability to trace the facts of information. There are differences in interest in finding out and understanding between elderly men and women